MINIMAL FLOW ANESTHESIA, ITS PLACE IN PERIOPERATIVE MANAGEMENT IN PATIENTS WITH HIATAL HERNIA - A. I. Denysenko; V. I. Cherniy (Клінічна та профілактична медицина, 2022)
Is relevant to study the perioperative use of minimal gas flow (minimal flow) during inhalation anesthesia in patients undergoing laparoscopic surgical interventions, in particular with hiatal hernia (HH).